The problem of Helicobacter pylori antibiotic resistance – overview and recent insights - Eder, Piotr (Lekarz POZ, 2016)
Helicobacter pylori infection, which is commonly registered worldwide, is believed to play a significant role in the pathogenesis of several diseases. There are multiple H. pylori eradication protocols, however their efficacy seems to be decreasing in the past years. In the current paper recent insights into antibiotic resistance in H. pylori eradication are presented, with emphasis on epidemiological and pathophysiological data.